2020
DOI: 10.1186/s13054-020-03218-5
|View full text |Cite
|
Sign up to set email alerts
|

Unspecific post-mortem findings despite multiorgan viral spread in COVID-19 patients

Abstract: Background: Post-mortem studies can provide important information for understanding new diseases and small autopsy case series have already reported different findings in COVID-19 patients. Methods: We evaluated whether some specific post-mortem features are observed in these patients and if these changes are related to the presence of the virus in different organs. Complete macroscopic and microscopic autopsies were performed on different organs in 17 COVID-19 non-survivors. Presence of SARS-CoV-2 was evaluat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
285
3
22

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 267 publications
(344 citation statements)
references
References 26 publications
25
285
3
22
Order By: Relevance
“…In the study reported by Solomon et al 46 and the study by Al‐Dalahmah et al, 48 the positive PCR results for SARS‐CoV‐2 in the CNS have not been confirmed in the same brain areas by immunostaining or in situ hybridization. In the study of Remmelink et al, 47 although SARS‐CoV‐2 RNA was found in 9 of 11 cerebral samples, autopsy examination did not found evidence of viral encephalitis or vasculitis. These discrepancies raised the question whether the positive PCR tests were false or not.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…In the study reported by Solomon et al 46 and the study by Al‐Dalahmah et al, 48 the positive PCR results for SARS‐CoV‐2 in the CNS have not been confirmed in the same brain areas by immunostaining or in situ hybridization. In the study of Remmelink et al, 47 although SARS‐CoV‐2 RNA was found in 9 of 11 cerebral samples, autopsy examination did not found evidence of viral encephalitis or vasculitis. These discrepancies raised the question whether the positive PCR tests were false or not.…”
Section: Resultsmentioning
confidence: 87%
“…Up to September 14, 2020, a total of 20 autopsy studies on neuropathology were retrieved, among which CNS detection of SARS‐CoV‐2 was negative in 12 (of 12) cases from three studies, 36,42,43 and positive in 58 (of 87) cases (66.7%) from nine studies, 46‐54 and unavailable for 109 cases in eight studies 35,37‐41,44,45 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, 93% of cases suffered from two or more comorbidities which is coherent with other autopsy studies beyond Hamburg. 28,[42][43][44] Interestingly, neither cardiac nor other comorbidities were associated with cardiac infection and even signs of virus replication in the myocardium were not more frequent in those with comorbidities. This is different in other organs, like the kidney, where cases with organ manifestation in general were more likely to have more comorbidities.…”
Section: Sars-cov-2 Infection Of the Heart -Susceptibility And Conseqmentioning
confidence: 99%